Strategi Pembentukan Sikap Disiplin Siswa di SMA Negeri 1 Kecamatan Akabiluru Lima Puluh Kota - Dzakiya Hartzani; Ike Sylvia (Universitas Negeri Padang, 2022)
This study aims to analyze the strategy of forming student discipline attitudes through integrating learning and school culture at SMA Negeri 1 Akabiluru District. In the process of forming student discipline attitudes, obstacles were encountered in its implementation. With these obstacles there are also solutions to these obstacles in the formation of attitudes in schools. This study uses a qualitative research approach, with the type of case study research, data collection by observation. in-depth interviews with 22 informants, and documentation studies. The data analysis technique uses the Miles and Huberman technique with the steps of Data Reduction, Data Display, and Withdrawal/Verification of Conclusions. The research location is in SMA Negeri 1, Akabiluru District, Lima Puluh Kota Regency. The results of this study show that the strategy in forming student discipline attitudes consists of integrating in learning and school culture. The strategy of forming student discipline attitudes through integration in learning at SMA Negeri 1 Akabiluru District is carried out in 2 ways, namely the formation of discipline attitudes through thematic instructional methods and the formation of disciplined attitudes through non-thematic instructional methods. Through thematic instructional with habituation of discipline in the classroom, it is carried out by conducting an initial diagnostic test to identify the student's character and the appropriate learning design. The strategy carried out by SMA Negeri 1 Akabiluru District through school culture is the habituation of new habits to school after the pandemic, providing exemplary behavior, collaborating with parents and the community, strengthening student discipline with extracurricular activities, habituation in participating in flag ceremonies and religious and branding activities. child friendly school.